Implementasi Keterampilan Pemecahan Masalah Matematis dalam Peningkatan Civic Dispositions Siswa - Ikhtiati Ikhtiati; Nisa Aulia; Ahmad Sayuti N; Hedia Rizki; Adzkya Milfa Laensadi (Journal on Education, 2023)
This research begins with exploring the theories and indicators of mathematical problem solving skills and how they relate to the increase in students' Civic Disposition which will be described in a descriptive qualitative manner. Furthermore, after obtaining indicators of mathematical problem solving skills, the researchers developed interview guides, questionnaires and observation sheets that were useful for seeing an increase in Civic Disposition. Before the distribution of questionnaires, interviews and observations was carried out, the instruments were validated first by experts so that they could be declared valid and worthy of dissemination. Then the process of determining the research sample was carried out, namely one of the Madrasah Ibtidaiyah in the city of Jambi. The research was conducted at MI Al-Munawwarah Jambi City. The results of the distribution of the questionnaire will be analyzed for each indicator of mathematical problem solving skills and their relationship with students' Civic Disposition. From the research conducted, it was found that in implementing these mathematical problem solving skills there is a relationship with an increase in students' civic disposition, seen from the character that is built in establishing cooperation in a problem solving. The process of learning mathematics which is related to the formation of civic character filled with other examples in different contexts will certainly be very beneficial for students in developing their mathematical skills such as reasoning and creative thinking in increasing students' civic disposition.